Credit rating and board evaluation of family firms - Ya-Fang Wang; Yu-Chu Hsieh (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: The purpose of this paper is to shed the light on board evaluation for following analyses that will explore whether and how does credit rating agencies react to board performance evaluation. Design/methodology/approach: To test our research questions, we hand-collect board evaluation information for Taiwan publicly firms from annual reports and firm websites for the years 2019 to 2021. Then, we use the ordered probit model to examine our research questions. Finding: First, our results show that there is a relationship between family firms and unfavorable ratings. However, effective board evaluation was shown to strengthen transparency and accountability in internal governance environment, thereby moderating such negative relationships. Second, when family firms are mandated to establish audit committees or change auditors, they are more likely to receive unfavorable ratings. Specifically, effective board evaluation moderates' negative effects on ratings and positively impacts rater perceptions. Third, rating agencies assign a more unfavorable rating to family firms that ignore gender diversity on audit committees, however, effective audit committee's evaluation could moderate the concern whether gender diversity on audit committees affect the effectiveness of corporate governance. Research limitations/implications: First, we focus on the context of family governance to examine the effect of board evaluation on credit ratings. Therefore, our findings may not be applicable to non-family firms. Second, we are not able to directly observe the mechanism of board evaluation because our study uses hand-collected data of board evaluation obtained from publicly available MOPS reports and website news. In addition, our sample period is limited from 2019 until 2022 due to the significantly higher hand-collecting cost of using board evaluation data. Third, with respect to our extended analyses on audit changes, we didn't consider the types of auditor changes because it is difficult to distinguish between auditor resignations and dismissals. Finally, although we include control variables consistent with prior studies, our research models may have not fully captured variables associated with credit ratings. Originality/value: First, our results contribute to the family firm literature on the relationship between corporate governance and economic consequence by focusing on the importance of board evaluation. Second, our findings can be useful to regulators and policy-makers in making governance policies aiming to mandate the establishment of audit committees' complementary rules by encouraging family firms to fulfill the board evaluation for improving the quality of governance environment. Third, our findings not only contribute to the auditing literature but also imply that the board's performance evaluation plays a positive factor in credit raters' considerations. Fourth, our findings contribute to the audit committee literature examining the effects of gender diversity and performance evaluation.
Keywords: G18; M41; M48; 330; board evaluation; credit rating; family firm